PENGARUH PEMBERIAN KAPSUL EKSTRAK GARLIK TERHADAP PERUBAHAN TEKANAN DARAH DAN JUMLAH TROMBOSIT PADA PENDERITA PREEKLAMPSI RINGAN - Irwanto, Yahya; Wahyudi, Imam; Soewarto, Soetomo (Fakultas Kedokteran Universitas Brawijaya, 2004)
The objectives is to investigate the efectivity of extract garlic capsule compared to standart therapytoward the changes of blood presure and thrombocyt level in the mild-preeclampsy patients. This study was a single-blind randomised clinical trial. The subject of study were the mild-preeclampsy pregnant women within 20 – 36 weeks of gestational age whose came to the Poli Hamil RSUD dr. Saiful Anwar. The subject divided into 2 groups, the treatment group received both of the standart therapy of mild-preeclampsy and extract garlic capsule, while the controlling grouponly received the standart therapy of mild-preeclampsy. After 2 weeks, the blood pressure and the trombocyt count was evaluated. Thesystolic blood pressure of the treatment group wasdecrease at average of 10.12 mmHg, from 140.25 ± 5.57 before treatment to 130.12 ± 10.84 mmHg after treatment, while in thecontrololling group there was an increase at average of 5.56 mmHg from 140.44± 6.14 mmHg to 146±13.81 mmHg. The T Test and ANCOVA analyzing showed a significant result (P value were 0.001 and0.0008).